Prowłączające zmiany w systemie polskiej edukacji – nowe możliwości, ograniczenia i wyzwania - Janiszewska-Nieścioruk, Zdzisława; Zaorska, Marzenna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
The past pro-inclusive actions and solutions in the education of people with disabilities, often can be perceived as highly positive, but, at the same time, they should lead to a critical and reflective approach towards them as well as their consequen- ces. In addition to the undoubted qualities, the article also points out their weaknesses and limitations that are primarily expressed in the totalization of organizational solutions and excessive dissemination, as well as reducing the quality of the pedagogue and teacher education. The above mentioned issues generate a need for fast, corrective actions in the Polish education system.